Analisis Faktor-Faktor Yang Memengaruhi Penurunan Risiko Cedera Pasien Akibat Jatuh Di Rumah Sakit Aulia Jakarta Selatan Tahun 2025 - Latifah, Siti Mutia; Sunadi, Apri; Pandjaitan , Costy (Jurnal sosial dan sains, 2025)
Patients fall down are one of the most common incident happens in the hospital environment, in which it can result in serious injury. Knowledge, attitudes, and caring behaviors are thought to influence the reduction of the risk of fall-related injuries. Therefore, this study aims to determine the effect of knowledge, attitudes, and caring behaviors on reducing the risk of fall-related injuries among nurses at Aulia Hospital, South Jakarta, by 2025. The study used a quantitative method with a cross-sectional design. The sample consisted of 89 nurses selected using a total sampling technique. The data was collected through questionnaires and analyzed using normality tests, univariate tests, bivariate tests, and multivariate tests. The results showed a significant relationship between knowledge and a reduced risk of injury from falls (p=0.013), attitude and a reduced risk of injury from falls (p=0.006), and caring behavior and a reduced risk of injury from falls (p=0.000). The multivariate test showed that caring behavior was the most dominant association with a reduced risk of injury from falls. The conclusion of this study is that knowledge, attitude, and caring behavior are important factors influencing the reduction in the risk of injury from patients fall down. Based on this research, it is recommended that the hospital provide on-site training, preferably in-house at the hospital, for all nurses working at RS Aulia. The training should cover fall risk mitigation and nurses' care practices. The hospital should also establish a team tasked with monitoring and evaluating nurses' efforts in daily activities to prevent patient falls. The team should also develop a guide book containing Standard Operating Procedures (SOPs) related to patient fall prevention.